128 TO BLEED OR NOT TO BLEED: THE INTRACEREBRAL HAEMORRHAGE MANAGEMENT QUESTION. (25th October 2022) - Murphy, B; Meagher, MK; Noone, I; Cassidy, T
Abstract: Background: Intracerebral Haemorhage (ICH) accounts for 9-27 per cent of all strokes. There are high rates of early case fatality and poor functional outcome. Clear guidelines and pathways exist around the management of ischaemic stroke. Pathways for the haemorrhagic stroke patient are lacking. Good evidence exists for early Blood Pressure (BP) management, reversal of Oral Anti-Coagulation (OAC) and admission to a Hyper-Acute Stroke Unit (HASU) in terms of improving outcomes. Methods: A retrospective cohort analysis was performed, looking at all the presentations with ICH over one calendar year. The factors measured included time to CT Brain, BP at presentation, documented target systolic BP of under 140mmHg, time to treatment of hypertension, number on OAC, OAC reversal, time to OAC reversal, admission to HASU. The findings were compared to standards outlined in the European Stroke Organisation and American Heart Association's ICH management guidance. Results: 76 patients were include (40 female). Mean age was 73, age range 34-93. median age 77. 44 were hypertensive on admission (20 info unavailable [u/a]). Of the 44, 34 had a documented target BP under 140mmHg (12 = n/a, 20 u/a). Time to treatment of hypertension was within 60 minutes for 3 patients. Of those that were hypertensive, 57 per cent were 75 or younger. 16 were on an OAC, of which 11 were appropriately reversed (3 u/a). Of the 11, 2 were reversed within 90 mins (7 u/a). Of those on an OAC, 75 per cent were over 75. 32 were admitted to HASU within 72h (all of these made it within 24h), (10 did not reach HASU, 3 reached HASU bed after 72h, 31 u/a). Conclusion: Management of ICH is variable and suboptimal. Our goal is to produce a written pathway which will be incorporated into our hyperacute stroke document, with a plan to re-audit.